Talking Race and Cyberspace. - Lovink, Geert (Frontiers: A Journal of Women Studies, 2005)
The article presents an interview with author Lisa Nakamura. Net is as racist as the societies that it stems from. She thinks that the Internet does more than mirror ideology from the culture at large; distinctive aspects of the Internet as a communication technology are lacking in other media, and its interfaces do as much to create particular kinds of identities as the Internet does to reflect them. The Internet hails its audiences in the same ways that texts have intended readers, that films and television shows have intended audiences, and that made environments are intended for particular users. And in its earlier stages the Internet was not hailing people of color; it assumed a normative white user and in fact often still does. The new media theorists talking about things other than or in addition to the Internet will result in more compelling theory. Nakamura does not think that the lack of compelling theory is due to a narrow focus on the Internet. Rather it is due to a lack of cultural studies-oriented instruction at the university level in the U.S., and the lack of institutional support and intellectual community for scholars in new media.